Worst-case analysis of electronic circuits based on an analytic forward solver approach. Issue 5 (2nd September 2019) - Schenk, Mario; Muetze, Annette; Krischan, Klaus; Magele, Christian
Abstract : Purpose: The purpose of this paper is to evaluate the worst-case behavior of a given electronic circuit by varying the values of the components in a meaningful way in order not to exceed pre-defined currents or voltages limits during a transient operation. Design/methodology/approach: An analytic formulation is used to identify the time-dependent solution of voltages or currents using proper state equations in closed form. Circuits with linear elements can be described by a system of differential equations, while circuits composing nonlinear elements are described by piecewise-linear models. A sequential quadratic program (SQP) is used to find the worst-case scenario. Findings: It is found that the worst-case scenario can be obtained with as few solutions to the forward problem as possible by applying an SQP method. Originality/value: The SQP method in combination with the analytic forward solver approach shows that the worst-case limit converges in a few steps even if the worst-case limit is not on the boundary of the parameters.